Purification and characterization of a polygalacturonase produced by Wickerhamomyces anomalus - Martos, M. A. (2014)
The aim of this work was to study the purification and physicochemical properties of an endo-polygalacturonase (PG) produced by Wickerhamomyces anomalus isolated from the citrus fruit peels. The enzyme was purified to homogeneity from the culture filtrate of W. anomalus grown on the yeast nitrogen base medium with glucose as carbon and energy source and citrus pectin as inductor. After anion-exchange chromatography and gel filtration chromatography, PG activity was eluted as a single peak, yielding 21% of the original activity. After dialysis and cation-exchange chromatography, only one fraction with PG activity was obtained, recovering 56% of initial enzyme activity and 1.3-fold increase in specific activity. The molecular weight of the enzyme was estimated as 43 kDa by the SDS-PAGE. The enzyme exhibited maximal activity at pH 4.2 and was stable over a pH range from 3.5 to 6.0 and up to 49°C for 10 h. The Vmax and Km values with polygalacturonic acid as substrate were 0.26 mmol/L. min and 0.173 mg/mL, respectively. Cations such as Cu+2, Fe+3, Mg+2, Mn+2 and Zn+2 did not show any significant effect on PG activity but K+ and Ca+2 reduced it. The purified PG was able to macerate cassava tissues.